The role of the end time in experimental asset markets - Kopányi-Peuker, Anita; Weber, Matthias (Journal of Corporate Finance, 2024)
There are hundreds of scientific articles on experimental asset markets. Almost all of them use a short and definite horizon. This may be one of the starkest differences between experimental settings and real-world financial markets, which usually have indefinite and comparatively long horizons. We analyze the implications of different end time assumptions in an asset market experiment in which we vary the length of the horizon and whether the end time is definite or indefinite. We find very similar price dynamics with recurring bubbles in all treatments.